Dissolved Cd, Co, Cu, Fe, Mn, Ni and Zn in the Arctic Ocean - Gerringa, L. J. A.; Rijkenberg, M. J. A.; Slagter, H. A.; Laan, P.; Paffrath, R.; Bauch, Dorothea; Rutgers van der Loeff, M.; Middag, R. (Journal of Geophysical Research: Oceans, 2021)
During the Polarstern (PS94) expedition, summer 2015, part of the international GEOTRACES program, sources and sinks of dissolved (D) Cd, Co, Cu, Fe, Mn, Ni and Zn were studied in the central Arctic Ocean. In the Polar Surface Water in which the TransPolar Drift (TPD) is situated, salinity and δ18O derived fractions indicated a distinct riverine source for silicate DCo, DCu, DFe, DMn and DNi. Linear relationships between DMn and the meteoric fraction depended on source distance, likely due to Mn-precipitation during transport. In the upper 50 m of the Makarov Basin, outside the TPD core, DCo, DMn, DNi, DCd and DCu were enriched by Pacific waters, whereas DFe seemed diluted. DCo, DFe, DMn and DZn were relatively high in the Barents Sea and led to enrichment of Atlantic water flowing into the Nansen Basin. Deep concentrations of all metals were significantly lower in the Makarov Basin compared to the Nansen and Amundsen, the Eurasian, Basins. The Gakkel ridge hydrothermal input and higher continental slope convection are explanations for higher metal concentrations in the Eurasian Basins. Although scavenging rates are lower in the Makarov Basin compared to the Eurasian Basins, the residence time is longer and therefore scavenging can decrease the dissolved concentrations with time. This study provides a baseline to assess future change, and additionally identifies processes driving trace metal distributions. Our results underline the importance of fluvial input as well as shelf sources and internal cycling, notably scavenging, for the distribution of bio-active metals in the Arctic Ocean.